Evaluation of German Merino ewe lambs’ temperament - Pajor, Ferenc; Láczó, Edina; Póti, Péter (Animal welfare, Ethology and Housing Systems (AWETH), 2007)
We evaluated temperament of German Merino ewe lambs using temperament test (temperament score: assessing behaviour of animals on a five-points scale, while spending 30 seconds on the weighing scale). 20 German Merino ewe lambs were fed-lot on ad libitum concentrate for 41 days. Animals originated from GAK Kht, Gödöllő (Pest County). The farm has been continuously controlled by Association of Hungarian Sheep Breeders. The examined lambs were taken part in Fattening Performance Testing. Temperament scores were examined three times under test, together with weighing. First measurement was at weaning, the second was at the end of fattening period, and finally the third was on 365th day. Body weights were taken prior to and after the fattening period, moreover in the 8th and 12th months. Growing curves were drawn by weight of animals. Daily weight gains under fattening period and under life time were calculated. Temperament score test was not related to the weight at weaning, therefore measurement of temperament was not affected by the weaning process (P > 0.10). 20 German Merino lambs were classified into three categories (calm, average and nervous) by mean temperament scores. Lambs with good temperament (1. category) had higher live weight at the end of fattening (33.0 kg), compared to average category (32.0 kg) and nervous category (29.4 kg). The average daily gain and average weight gain under life time showed a similar tendency among good category (298.8 g/day, 338.2 g/day), average category (265.2 g/day, 311.6 g/day) and nervous category (238.7 g/day, 304.5 g/day). Calm ewes had better growing rate till one year of age, than nervous ewes. This difference was showed by different slopes (b) of growing curves. To sum up, lambs with calm temperament were better at fattening performance compared to lambs with poor temperament. Accordingly, the selection work may be improved by the results of temperament measurement.